1968
DOI: 10.1039/tf9686401206
|View full text |Cite
|
Sign up to set email alerts
|

Precise cryoscopic determination of osmotic coefficients for solutions of some alkali metal salts in dimethyl sulphoxide and in sulpholane

Abstract: An apparatus is described for the precise measurement of freezing-point depressions for nonaqueous solutions by a heating curve method. The apparatus has been used for measurements on solutions in dimethyl sulphoxide and in sulpholane (tetrahydrothiophene-1 ,l-dioxide), the relevant physical properties of which are critically discussed. Osmotic coefficients have been determined with an accuracy of 0.2-1 % for solutions of some alkali metal perchlorates and of lithium chloride. The salts studied behave differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…[2] is replaced by a factor of 4, and when combined with Eq. [1] this yields Oobs 8eorr = -- [5] 1 --4Q with the same value of Q as derived above.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…[2] is replaced by a factor of 4, and when combined with Eq. [1] this yields Oobs 8eorr = -- [5] 1 --4Q with the same value of Q as derived above.…”
Section: Resultsmentioning
confidence: 64%
“…A more direct comparison can be made in terms of the function (8) Fig. 3 our results are compared with those of Dunnett and Gasser (3) and Garnsey and Prue (5). By numerical integration we also obtained j as a function of m, corresponding to the best fit to the emf data ( Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Precise and extensive cryoscopic determinations of molal freezing point depressions of organic solutes in Sulfolane by Della Monica et al (14) revealed that the constants for benzoic acid from 0.1 to 1 M are identical to those of diphenylmethane, naphthalene, and benzene which are not expected to dimerize. We also found that the molal freezing point depression constant for 0.01 M acetic acid in Sulfolane as determined by using the LKB calorimeter was 64 + 2" compared to normal values of 65" (14) and 64" (15) for nonassociating substances. Furthermore, the heats of mixing with Sulfolane given in Table 1 for acetic acid and the substituted acetic acids, in the range 0.02 to 0.4 M acid, are' constant within 50.02 kcal per mol acid.…”
Section: Hydration Constants Of the Acidsmentioning
confidence: 77%
“…The cell capacitance was measured by a substitution method using a General Radio 1606-B bridge and Type 722-D and 1422-ME precision variable capacitors. The cell constants were determined from measurements made with air (7), benzene (8), PC (6), and dimethylsulfoxide (9). A leastsquares fit gave where C is the measured capacity and E is the static dielectric constant.…”
Section: Experimental Section ( a ) Materialsmentioning
confidence: 99%